Factores de riesgos físicos químicos, biológicos y ergonómicos a los que está expuesto el personal auxiliar de Enfermería del Hospital General Isidro Ayora de Loja noviembre 2014 -junio 2015 - Jiménez Cumbicus, Tatiana Cecibel (2015)
For the (WHO) World Health Organization (2010), and the (PAHO) Panamerican Health Organization (2008), the health promotion in the workplace includes performing a series of politics and activities in the workplace designed in order to help employers and workers at all levels to increase control over their health and improve it, promoting the productivity and competitiveness of companies and contributing to economic and social development of countries. For the health promotion in the workplace call together the participation of workers, employers and other social actors interested in the implementation of initiatives agreed jointly to the health and well-being of the workforce between the declared risks include those related to the Organization of work (high level of attention, high work rate and little participation in aspects of work organization) also emphasize some factors associated with the physical risks, static position or forced and repetitive movements. The present research of descriptive and transversal type, suggest the objectives in order to determine the physical risks, chemicals, biologicals and ergonomic that the nursing personal are exposed, 59 people participated in the studies, whose works in the surgery areas, Pediatrics, Internal Medicine, Obstetrics – Gynecology and General Consultation, in order to collect the data was necessary to apply the survey. The results obtained were: as physical risks, desconfortable working environment, reduced physical space, and noise: as chemical risks, 23% alcohol exposure, iodized alcohol and savlon: the biological risks are related to the handling urine exposure , injury secretions, ergonomic risks the foot position to 81%, the 66% does not break and 29% rest less than 15 minutes. KEYWORDS: risk factor, biological risk, physical risk, chemical risk, ergonomic risk, nursing assistant.